Health inequalities in Slovakia assessed by the Health Index: Unveiling regional disparities and their impact on the population - Katarína Vilinová; Kristína Bullová (Hungarian Geographical Bulletin, 2025)
Health inequalities represent a significant social problem not only in the world but also in Slovakia. They are conditioned by several factors such as socio-economic status, geographic location, age, ethnicity and access to health care. Inequalities in the general health status of districts can be assessed using selected determinants. A composite indicator (Health Index) was used to quantitatively assess health inequalities in the districts. This Health Index consists of 8 assessment domains and 50 indicators at the district level (LAU1) in the Slovak Republic. We evaluated the data using the multi-criteria decision-making method (WSA method). The findings suggest that when districts are assigned different weights, changes occur in the health index values. Identifying problem regions is therefore very important. The health situation in Slovakia is not uniform and the results of the research showed differences between the West and the East. The districts located in the southern part of Slovakia, which achieved the lowest values of the index, can be included among the areas at risk in the context of the Health Index assessment. In order to mitigate them, it is necessary to improve access to health care, invest in prevention and improve the economic conditions of the population. It is also essential to propose possible solutions. These include improving access to preventive care and health education. The next step is reforms in the health system. These aim to reduce inequalities and improve public health.